Long-term consumption effect of eurycoma longifolia jack on histopathological changes in the vital organs in rats - Alfaqeh, Hamoud Hussein Mohammed (AENSI Journals, 2014)
Introduction:The use of Eurycoma longifolia Jack (ELJ)has increased in Southeast Asia especially Malaysia where it is widely used as power enhancement agent. Its use has become nationwide in Malaysia and Indonesia in daily life as beverage to enhance energy and stamina especially among males. However, its effect on the safety of vital organs of the body has not been studied properly.Thus, the main objective of this study was to determine whether long-term use of ELJ has side effects on the vital organs such as Pancreas,Liver and Kidney in rats. Materials and methods: Three different concentrations of aqueous extract of ELJ were prepared and dissolved in distilled water. A total of 32 Sprague-Dawley male rats were used and randomly divided into three test groups and control. The test groups were given different doses (low dose 250 mg/kg bw, medium dose 500mg/kg bw and high dose 1000 mg/kg bw) of aqueous extract of ELJ,respectively. Control group was given distilled water alone. Doses were given orally and daily for 5 weeks. After 5 weeks,animals were sacrificed; whole liver tissues were obtained, fixed in 10 percent formaldehyde overnight for histological examination. Result: Histological observations showed mild to moderate degrees of hemorrhage,hepatocytes degeneration and severe fatty changes in liver tissue of the test groups treated with ELJ as compared to control. Conclusion: In conclusion, the long-term daily consumption of ELJ in large quantity as beverage may cause fatty changes, hemorrhage and hepatocytes degeneration in the liver tissue. The Pancreatic tissues on the three groups treated with different concentration doses do not show any necrosis or inflammation in the treated groups.